The Utilization of Modified Cassava Flour (Mocaf) Industry Waste and Peat as Carrier of Nitrogen-Fixing Bacteria and Phosphate Solubilizing Bacteria Inoculant - RETNO ROSARIASTUTI; SUMANI SUMANI; SUPRIYADI SUPRIYADI; MUHAMMAD ARDIAN NURSETYAWAN; PRAMUSITA YOGA DANISWARA (Microbiology Indonesia, 2017)
Fertilizer demand in Indonesia increase for increasing agricultural production.Biofertilizer is organic fertilizer with the addition of specific microorganisms which are expected to reduce the amount of inorganic fertilizer. Carrier material plays an important role in maintaining the viability and storage period. Peat is used as a biofertilizer carrier for  a long time. Solid waste of Modified Cassava Flour (Mocaf) which is the remainder of mocaf industry has great potential as a carrier material of good biofertilizers,  because of its nutrient content. The aim of this study was  determining the potential of mocaf solid waste and its combinations with peat as the carrier in supporting the growth of Nitrogen-fixing Bacteria (NFB) and Phosphate Solubilizing Bacteria (PSB) during the incubation  of microorganisms. The experiment was conducted at the Laboratory of Soil Biology and Biotechnology, Faculty of Agriculture of Sebelas Maret University (UNS) using completely randomized design (CRD) with two factors of a carrier and incubation time as the experimental design. There  were  three  types of  carrier  which  have different  combination. The base material were solid  waste  of  Mocaf  industry   and  peat.  All materials  of carrier  were  mixed and sterilized, than inoculated by Nitrogen- Fixing  Bacteria (NFB)  and  Phosphate Solubilizing  Bacteria (PSB) and incubated  for  60  days. The  growth of  bacterias were analyzed  every 15  days  and  the  chemical composition  of  carrier  were  analyzed  at  the begin and the  end of  research   (incubation).    The results indicated that the incubation time significantlyaffected viability of NFB and PSB. Until 60th day incubation time, still showed the increasing growth of NFB and PSB.